OCC-ID: New Broadcasting Service-Based Cloud Model and Image Sensor Communications - Thithanhnhan Le; Nam-Tuan Le; Yeong Min Jang (International Journal of Distributed Sensor Networks)
In recent decades, the main data traffic of mobile communication is based on the RF technology. Even though the efficiency from optimization for utilization or reuse is applied, there is a limitation of increased traffic demand of RF communication. Visible light communication (VLC) is a new technology that can cooperate with RF to address this limitation. The standard for VLC was published in 2011 as IEEE 802.15.7, which defined the specifications for the MAC layer and the PHY layer. This standard was one of the first for this technology. The decoded operation from emitting light at the receiver in IEEE 802.15.7 is mainly based on the photodetector. However, with the development of image sensors (matrix of photodiodes) on smart devices, the amendment of IEEE 802.15.7 specification is considered. The extension will focus mainly on image sensor communications, named optical camera communications (OCC). In this paper, we analyze the performance of a camera communications system based on different types of image sensor architecture. Then, we suggest OCC-ID, a new application for broadcasting service using camera communications and the cloud model. The proposed architecture is a typical deployment scenario of camera communications.